Exploring Combination Therapies in AD: Additive Effects of the QPCT Inhibitor Varoglutamstat and Aducanumab on Aβ Pathology and Biomarkers In Vivo. (20th December 2022) - Hoffmann, Torsten; Schenk, Mathias; Gnoth, Kathrin; Ilse, Victoria; Brunner, Daniela; Rahfeld, Jens‐Ulrich; Schilling, Stephan; Schaeffer, Michael
Abstract: Background: Pyroglutamate‐ 3Aβ (N3pE), a toxic Aβ variant formed by the activity of glutaminyl gyclase (QPCT) has been shown to play a pivotal role in the development and progression of Alzheimer's disease (AD). Recently, we demonstrated that a combination of the QPCT inhibitor varoglutamstat (PQ912) with the N3pE‐specific antibody m6 has an additive effect on lowering of N3pE in vivo . Here, we analyzed whether a similar additive effect could be achieved when combining varoglutamstat with the Aβ‐aggregate‐specific antibody aducanumab. Method: Nine‐months old APPxhQC mice were treated with either varoglutamstat (1.6 g/kg chow, ad libitum), chimeric aducanumab (chAdu, ≈10 mg/kg i.p. weekly) or a combination of both for 16 weeks. Brain Aβ accumulation (ELISA and immunohistochemistry) and AD biomarkers in the water‐soluble brain fractions (neurogranin, BACE‐1, YKL‐40; ELISA) were analyzed and compared to a vehicle‐treated group. Result: Treatment with either varoglutamstat or chAdu significantly reduced the accumulation of both total Aβ and N3pE in the brain. The effect of chAdu was more pronounced for total Aβ (‐35% vs. ‐21% for varoglutamstat), while varoglutamstat treatment resulted in a stronger decrease of N3pE (‐28% vs. ‐19% for chAdu). The combination treatment generally led to a stronger decrease of Aβ vs. single agent treatment (Bliss combination index (CI) = 0.88 for soluble Aβ42 and 1.23 for insoluble Aβ42). For insoluble N3pE, the observed effect was nearly additive (CI = 1.09). Treatment with chAdu, varoglutamstat or both had different effects on the analyzed AD biomarkers. chAdu treatment significantly decreased BACE‐1 protein levels (‐30%), while varoglutamstat treatment significantly reduced levels of the brain inflammation marker YKL‐40 (‐27%), which is in line with earlier clinical Phase 2a study results. Conclusion: Our data indicate that a combination of agents with different modes of action such as aducanumab, an Aβ aggregate‐specific antibody and varoglutamstat, a small molecule designed to block formation of toxic, aggregation‐prone N3pE, can act additively to decrease total Aβ and N3pE levels in the brain. Our results also provide a rationale for investigating different potential combination regimens, including an initial antibody‐mediated Aβ clearance followed by long‐term suppression of N3pE formation and inflammation by varoglutamstat ("treat and maintain").